1995
DOI: 10.1038/jcbfm.1995.79
|View full text |Cite
|
Sign up to set email alerts
|

Changes inN-Acetyl-Aspartate Content during Focal and Global Brain Ischemia of the Rat

Abstract: N-Acetyl-aspartate (NAA) is almost exclusively localized in neurons in the mature brain and might be used as a neuronal marker. It has been reported that the NAA content in human brain is decreased in neurodegenerative diseases and in stroke. Since the NAA content can be determined by nuclear magnetic resonance techniques, it has potential as a diagnostic and prognostic marker. The objective of this study was to examine the change of NAA content and related substances following cerebral ischemia and compare th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
63
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 43 publications
9
63
0
Order By: Relevance
“…Sager and colleagues have used multiple techniques to study NAA levels and the levels of other metabolites in experimental ischemic injury in rodents. HPLC analyses of focal and global ischemia in rats indicated a slightly more rapid decline in NAA levels in focal ischemia, reaching approximately 50% of controls in 8 hours (Sager et al, 1995). The most conspicuous difference between focal and global ischemia was that aspartate levels decreased in focal ischemia, but were increased significantly over the course of 24 hours after global ischemia, possibly indicating that global ischemia brings NAA and its degratory enzyme ASPA, normally segregated in distinct compartments, into contact.…”
Section: Magnetic Resonance Spectroscopy and Imaging Of Naamentioning
confidence: 95%
See 1 more Smart Citation
“…Sager and colleagues have used multiple techniques to study NAA levels and the levels of other metabolites in experimental ischemic injury in rodents. HPLC analyses of focal and global ischemia in rats indicated a slightly more rapid decline in NAA levels in focal ischemia, reaching approximately 50% of controls in 8 hours (Sager et al, 1995). The most conspicuous difference between focal and global ischemia was that aspartate levels decreased in focal ischemia, but were increased significantly over the course of 24 hours after global ischemia, possibly indicating that global ischemia brings NAA and its degratory enzyme ASPA, normally segregated in distinct compartments, into contact.…”
Section: Magnetic Resonance Spectroscopy and Imaging Of Naamentioning
confidence: 95%
“…There is an approximate 10% decline in NAA over the first 6-8 hours after occlusive stroke, with a T ½ of about 15 hours for the remaining 50%. The lowest in vivo levels of NAA are observed only after 50-70 hours in animal studies (Higuchi et al, 1996;Sager et al, 1995). Animal studies into the early response to experimental ischemia have shown that increases in lactate can be observed by MRS within 40 minutes of onset, and small decreases in NAA/Cr were observed at one hour (Yi et al, 2002).…”
Section: Magnetic Resonance Spectroscopy and Imaging Of Naamentioning
confidence: 99%
“…However, NAA was undetectable in the blood with ischemic stroke, 70 so the direct excretion of NAA into the residual blood flow within the ischemic core can be expected to play only a minor role on NAA attenuation in acute sgate of ischemia. Furthermore, no rise in NAA levels were found in the CSF of rat models of focal ischemia 71,72 despite its massive release into the ECS. These results suggest a previously unknown NAA catabolic pathway in brain tissue that is activated during ischemia.…”
Section: Concept Of Experimental Ischemic Strokementioning
confidence: 94%
“…Indeed, complete global ischemia achieved by decapitation, in which there is a lack of residual blood flow, leads to a reciprocal accumulation of aspartate and acetate over NAA loss. 72 Aspartacylase activated by Ca 2+ accumulated in cytoplasm as a result of ischemia may play the dominant role in NAA catabolism in complete global ischemia. 68 Paradoxically, the levels of both aspartate and acetate decreased in the ischemic lesion during focal ischemia.…”
Section: Concept Of Experimental Ischemic Strokementioning
confidence: 99%
See 1 more Smart Citation